Good night tiger - Knapman, Timothy (Tiger Tales, 2016)
Emma is trying to sleep, but the animals in her wallpaper are making too much noise! The gorilla bellows, the hippo stomps, the elephant trumpets, and tiger growls. "Go to sleep!" Emma tells them. "We've tried and tried, but we can't!" replies the tiger. Then Emma gets an idea. Can she help the noisy animals settle down so that everyone can get to sleep?